EDUCATIONAL REFORM IN OPTIMIZING STUDENT ACADEMIC ABILITY - Destrianjasari, Sherin; Annur, Saipul; Handayani, Tutut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In the era of information technology in the 21st century, as now requires everyone to be innovative, education is also a field that demands renewal so that the system or application of education is not outdated. In completing the research results obtained from the library both from sources in the form of books, dictionaries, and journals. The conclusion of this study is that innovation is a process of renewal and change. The world of education requires renewal to continue to grow and be able to keep abreast of developments in other fields. Renewal in the world of education must be measurable and continue to increase at a better level. High quality education is related to knowledge and technology as well as creative output. Educational innovation Relates to the use of technology. Technology plays an important role in contributing to innovation in the field of education.